2006
DOI: 10.1037/0278-7393.32.6.1274
|View full text |Cite
|
Sign up to set email alerts
|

Roles of egocentric and allocentric spatial representations in locomotion and reorientation.

Abstract: Four experiments investigated the nature of spatial representations used in locomotion. Participants learned the layout of several objects and then pointed to the objects while blindfolded in 3 conditions: before turning (baseline), after turning to a new heading (updating), and after disorientation (disorientation). The internal consistency of pointing in the disorientation condition was relatively high and equivalent to that in the baseline and updating conditions, when the layout had salient intrinsic axes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
129
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(143 citation statements)
references
References 38 publications
13
129
1
Order By: Relevance
“…(2006) interpreted their results according to the logic that egocentric representations are used when the configuration error effect is observed and that allocentric representations are used when it is not. They concluded that, without vision, an egocentric system may be used when reliable allocentric representations cannot be formed or are of low fidelity, as is the case when an array of objects is irregular and no integrative, external viewpoint of the array is allowed beforehand.While the results of Holmes and Sholl (2005) and Mou et al (2006) may cast doubt on Wang and Spelke's claim that updating is performed primarily on egocentric object representations, the current study uses Wang and Spelke's paradigm to search for more concrete evidence of allocentric representations. Rather than taking the absence of a disorientation associated increase in configuration error as evidence for allocentric encoding, we conducted distinct analyses seeking evidence of both egocentric and allocentric encoding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2006) interpreted their results according to the logic that egocentric representations are used when the configuration error effect is observed and that allocentric representations are used when it is not. They concluded that, without vision, an egocentric system may be used when reliable allocentric representations cannot be formed or are of low fidelity, as is the case when an array of objects is irregular and no integrative, external viewpoint of the array is allowed beforehand.While the results of Holmes and Sholl (2005) and Mou et al (2006) may cast doubt on Wang and Spelke's claim that updating is performed primarily on egocentric object representations, the current study uses Wang and Spelke's paradigm to search for more concrete evidence of allocentric representations. Rather than taking the absence of a disorientation associated increase in configuration error as evidence for allocentric encoding, we conducted distinct analyses seeking evidence of both egocentric and allocentric encoding.…”
mentioning
confidence: 99%
“…Another possibility suggested by Wang and Spelke is that disoriented participants respond on the basis of remembered egocentric images formed from and corresponding to the learning heading. Brou and Doane (2003), Mou et al (2006), and others have shown that certain individuals do use this strategy in this paradigm. However, the number of these individuals included in the current analyses appears to be relatively small as indicated by the random distribution of heading errors observed in the disorientation conditions (as discussed in Footnote 5).…”
mentioning
confidence: 99%
“…Spatial navigation is the process of determining and maintaining a course or trajectory to a goal location accurately and efficiently [9] and is a requirement of daily life. Behavioral studies of spatial navigation indicate two important aspects for navigation involving allocentric or egocentric representations [10,11]. Allocentric representations (e.g., South or North) are linked to a reference frame based on the external environment and independent of one's current location in it, while egocentric representations (e.g., left or right) reference spatial locations in the external world with respect to individual body space.…”
Section: Spatial Navigation "Where Am I?" "Where Are Other Places Witmentioning
confidence: 99%
“…To provide further insight into the factors that cause these differences, we calculated the signed pointing errors for each trial. Then, following the analysis method introduced by Wang and Spelke (2000) and adapted by Mou, McNamara, Rump, and Xiao (2006;see also Xiao, Mou, & McNamara, 2009;Xiao & Zhang, 2013), we computed each participant's heading error, pointing variability, and configuration error from each imagined perspective. This type of analysis of pointing errors had not been conducted in the previous studies of map learning discussed earlier (e.g., Giudice et al, 2011;Presson et al, 1989;Presson & Hazelrigg, 1984), and so is novel to this study.…”
Section: Analysis Of Sources Of Pointing Errorsmentioning
confidence: 99%